Computing with words via Turing machines a formal approach. - Huaiqing Wang
Computing with words (CW) as a methodology, means computing and reasoning by the use of words in place of numbers or symbols, which may conform more to humans' perception when describing real-world problems. In this paper, as a continuation of a previous paper, we aim to develop and deepen a formal aspect of CW. According to the previous paper, the basic point of departure is that CW treats certain formal modes of computation with strings of fuzzy subsets instead of symbols as their inputs. Specifically, 1) we elaborate on CW via Turing machine (TM) models, showing the time complexity is at least exponential if the inputs are strings of words; 2) a negative result of (6) not holding is verified which indicates that the extension principle for CW via TMs needs to be re-examined; 3) we discuss CW via context- free grammars and regular grammars and the extension principles for CW via these formal grammars are set up; 4) some equivalences between fuzzy pushdown automata (respectively, fuzzy finite-state automata) fuzzy context-free grammars (respectively, fuzzy regular grammars) are demonstrated in the sense that the inputs are instead strings of words; 5) some instances are described in detail. Summarily formal aspect of CW is more systematically established more deeply dealt with while some new problems also emerge.
Keywords: Turing machines; Computing with words; Context-free grammars; Extension principle; Formal approach; Formal grammars; Fuzzy finite-state automata; Fuzzy grammars; Fuzzy pushdown automata; Fuzzy subsets; Regular grammars; Time complexity